CONCEPT FOR SUPPORTING THE DEVELOPMENT OF TEACHER EDUCATION FOR THE PERIOD (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article determines the importance of the technological approach in the process of teaching literature at school. Considering the models of a modern teacher available in didactics, the authors determine the use of pedagogical technologies as the most important component of professional teacher competence. Studying in detail the concept of “pedagogical technology”, the authors identify its features based on comparison with methodology, defend their own opinion in a discussion on the issue of technologization of literature as an educational subject, characterize the program for the use of technology in educational activities